INOVASI MANAJERIAL KEPALA SMK BERBASIS PESANTREN (Studi Multi Kasus SMK Pesantren di Banyuwangi) - Kholilur Rahman (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2015)
This preliminary study aims to identify, describe and analyze innovation-based head of vocational schools as well as their implications, particularly with regard to managerial innovation. Reality later showed the proliferation of schools in Banyuwangi establish formal educational institutions, particularly vocational schools (SMK). Though conceptually management, between schools and vocational embracing the concept of different management. Management schools tend to be centralized, while the vocational school as a formal educational institution adheres desentralitik management system. Thus, it does require changes in the system, both organizationally and managerially. One side of the Head of SMK should be able to secure the values uniquely pesantren as the